Application of Sentiment Analysis in the Reshot Method to Improve User Experience of the Hijra Bank Application - Ma'arif, Ridwan Ahmad; Triayudi, Agung (SAGA: Journal of Technology and Information System, 2024)
The first stage in simplifying User Experience (UX) using the RESHOT method is Refine the Challenge. This stage is carried out so that design practitioners know the problems or needs of application users through product research. However, the product research methods that can be carried out at this stage are very diverse and require time. This research aims to explain a product research method that can be used by design practitioners easily and quickly, namely the sentiment analysis method with the Naïve Bayes algorithm. Naive Bayes is a classification method based on simple probability. The results of this analysis will be used as a reference for improving UX using the RESHOT method on the Hijra Bank application. The results of product research using sentiment analysis obtained 2711 opinions originating from tweets on Twitter and user reviews of the Hijra Bank application on Google Play. Of the 2711 opinions, 149 had negative sentiment, with the most frequently mentioned opinions being "Customer" and "Data" with an analysis accuracy of 92%. The results of this analysis are converted into a hypothesis, which will later become a reference in designing interfaces using the RESHOT method.